Fish Allergy: Recent Advances in Diagnostics and Innovative Processing Technologies for Allergen Management - Riya Liuhartana Nasyiruddin; Husnain Raza; Willard Burton Navicha; Abdellatief A. Sulieman; Elok Ilunanwati (CV. Media Inti Teknologi, 2025)
Background: Fish allergy is a major immunological concern that affects sensitive individuals worldwide, primarily due to stable fish proteins such as parvalbumin. The allergenic potential differs across species and is influenced by environmental exposure and food processing. Aims and Scope: This review explores current diagnostic approaches, allergenic protein characterization, and recent innovations in fish processing technologies aimed at reducing allergenic risks. Methods: A critical evaluation of recent studies was conducted to assess immunological properties of fish allergens, diagnostic tools (e.g., IgE-based assays, species-specific PCR), and the impact of physical, enzymatic, and non-thermal processing on allergenicity. Results: Major allergens like Gad c 1 exhibit high heat stability, while those in tuna or salmon show reduced allergenicity after cooking. Diagnostic tools, including molecular assays, provide accurate identification of allergens and fish species, essential for risk management. Processing methods such as high pressure treatment, thermal glycation, enzymatic hydrolysis, and washing can modify proteistructures and reduce IgE-binding capacity. Additionally, poor-quality raw fish and impropefermentation may elevate histamine and biogenic amine levels, increasing allergic risk. Conclusion: Fish allergy management requires a combined understanding of allergen structure, reliable diagnostics, and processing interventions. Emerging technologies hold promises for developing hypoallergenic fish products and ensuring consumer safety through improved allergen detection and control strategies.